Improving transitions of care for patients on warfarin: The safe transitions anticoagulation report. Issue 9 (4th September 2015) - Dunn, Andrew S.; Shetreat‐Klein, Avniel; Berman, Jeremy; Cho, Hyung J.; Stein, Laura; Lewis, Chenelle; Hamilton, Sharla; To, Simon; Francaviglia, Paul; Kannry, Joseph
<x xml:space="preserve">Abstract</x> Adverse drug events are common during the transition period after hospitalization, and anticoagulants are among the medication classes for which the incidence is highest. We aimed to develop a concise report to improve the timeliness of international normalized ratio (INR) testing and quality of warfarin management posthospitalization. We developed the Safe Transitions Anticoagulation Report (STAR), which contains essential information on anticoagulation and is embedded in the discharge summary, and implemented the report and associated workflow in a tertiary care hospital within an integrated healthcare system. We performed a retrospective administrative database review of 505 patients in the preintervention period and 292 patients in the intervention period who were discharged on warfarin and were established patients at an affiliated ambulatory practice. There was no change in the frequency of obtaining an INR value within 10 days of discharge (41.4% and 47.6%, respectively, P = 0.09), and no increase in attaining a therapeutic INR level within 10 days of discharge (17.0% and 21.2%, respectively, P = 0.14). Ambulatory clinicians reported that the STAR improved "workflow and efficiency" (58%) and "patient safety" (77%), and led to an altered warfarin dose for 34% of survey respondents. Our study found that a concise anticoagulation report embedded in the discharge summary was perceived by ambulatory physicians as improving patient safety, but had no impact on clinical outcomes, suggesting that this electronic medical record tool would need to be a component of a broader multifaceted intervention to be effective. Journal of Hospital Medicine 2015;10:615–618. © 2015 Society of Hospital Medicine